If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6m+5=19(m=(-2))
We move all terms to the left:
6m+5-(19(m)=0
| 2(3x-4)-(x-5)=31 | | 9m-4m=45 | | |6x+12|=24 | | 2(x+3)=8(2x-6) | | -15y-26=0 | | 867+x=938 | | 8d=5 | | 48-6=x | | 7(x+10)=-2(-11x+7)+9 | | 4z+9z=39 | | 2(12+2r)=80 | | X^2-12x+12x+21=0 | | y=-(2/3)(8)+13 | | 16.35+x=39.75 | | 2x-9+2x+4+x=180 | | 15(r+3)=60 | | 5(1+6k)+5(1+k)=45 | | x^2-19=42 | | -7(x-7)=4 | | 15.91+0.09x=16.41-0.12x | | 8q-3q+15=40 | | 3r+5-4=16 | | -4(4-6)-(6-2v)=10 | | -x=4+x+6 | | 4p-9=37 | | 8x2-26x-7=0 | | 5^(x+2)+2*5^(x-1)=127 | | 5^(x+3)+2*5^(x-1)=127 | | 3x+3+5x-15=48 | | 18x-1+55=180 | | 5(4+2r)-4(2r-3)=40 | | 0=2/3x+10 |